Critical Soil Health Parameters to Improve Crop Production - Gretchen F. Sassenrath; Bruno C. Pedreira; Carlos B. Pires (Kansas Agricultural Experiment Station Research Reports, 2023)
Soil health is a critical determinant of plant performance. This manuscript describes how the physical, chemical, and biological components within the soil interact to create good soil health. Soil structure is important to provide support for plants, nutrient and water cycling, decreased compaction, and more efficient carbon storage. Measurements of soil properties are presented that can be done in the field on any soil.
Keywords: soil nutrient cycling; soil carbohydrates; soil aggregates; soil organic matter; soil health; aggregate stability; erosion simulation